(untitled) (World Bulletin of Management and Law, 2022)
The current study aims to employ innovative organizational capabilities (performance goals, personal innovation, learning goals, incomprehension, innovative), In developing the innovative work behavior of (generating ideas, promoting ideas, implementing ideas) in a sample of the faculty members in the Islamic University/Iraq. In order to collect the data, a sample of the faculty members in the Islamic University/Iraq was surveyed and 192 questionnaires were presented with a valid questionnaire for analysis, and it also claimed that it was necessary to disclose the nature of the results the research seeks to achieve in order to use a set of statistical tools, represented by the Kronbach Alpha coefficient, the arithmetic mean, and the standard deviation. Pearson correlation coefficient, regression coefficients), The results showed a statistically significant correlation and impact between innovative organizational capabilities and innovative work behavior, demonstrating the university’s interest in improving the abilities of faculty members during the delivery of the educational service by developing their abilities using modern classroom management techniques